PENERAPAN MODEL PEMBELAJARAN OSBORN UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LAJU REAKSI - Fachri Reza Ramadhan; John Azmi; Herdini Herdini (Jurnal Pendidikan Kimia Universitas Riau, 2021)
This research is aimed to determine the increase in student learning achievement toward the implementation of Osborn learning model on the subject of rate of reaction. This research was conducted at Muhammadiyah 1 Pekanbaru on class XI MIA SMA. The research is an experimental study with randomized control group pretest-posttest design. The sample of the study was students of class XI MIA 3 as an experimental class and students in class XI MIA 4 as a control class. The experimental class was applied to the Osborn learning model, while the control class was not treated. The data analysis technique used was the t-test. Based on the results of the data analysis test tcount> ttable is 9,141 > 1.670, meaning that the application of Osborn's learning model can improve student learning achievement on the subject of rate of reaction in class XI MIA SMA Muhammadiyah 1 Pekanbaru.